Fears, doubts and joys of not belonging - Fishkin, Benjamin Hart; Ankumah, Adaku T.; Ndi, Bill F. (Langaa Research & Publishing CIG, 2014)
This book is an opportune warning that alienation, estrangement and intentional diminishment serve as a cancer upon those who disburse it. The outsider suffers by being alone; the insider suffers even more by being forever known as a hypocrite who perpetuates dystopia. It uses literature as a hothouse for poisonous potted plants, the workings of a mind in turmoil and the exploration of a society or societies that seems to derive pleasure from others' ruin. Fears, Doubts, and Joy of Not Belonging considers themes that are biblical in scope from different societies and historical epochs. It is a sobering spiritual enlightenment of a child's "silent treatment" in adult form. The text complements language engineers and social scientists who are on a quest or search for how the individual responds to pressure that is unexpected, ill-conceived and in desperate need of alleviation. Not only does this particular type of cancer differ from the type a surgeon can treat, the stage at which this malady is diagnosed causes far more problems than if it were dealt with head on. Pursuing numerous examples of estrangement, this diverse text delves into a wide spectrum of human behavior while coming to the realization that these problems are universal and have been with us for a long, long time. The purpose of resistance, individuality and personal identity is to rise above these obstacles without losing hope, resilience or optimism